MicroRNA-21 Overexpression Promotes the Neuroprotective Efficacy of Mesenchymal Stem Cells for Treatment of Intracerebral Hemorrhage - Zhang, Heyu; Wang, Yanzhe; Lv, Qing; Gao, Jun; Hu, Liuting; He, Zhiyi (Frontiers in Neurology, 2018)
Intracerebral hemorrhage (ICH) is a kind of serious cerebrovascular diseases with high morbidity and mortality, which has no effective treatment at present. Mesenchymal stem cell (MSC) plays therapeutic roles in different nervous diseases experimental models and shows a potency in stem cell therapy for human. However, many deficiencies in MSC treatment still need to be addressed, such as only a few MSCs survived post transplantation. Our previous study has found that miR-21 down-regulated in ICH patients’ blood and brain tissue. We aimed to examine the therapeutic efficacy and mechanisms of miR-21-overexpressing MSCs on intracerebral hemorrhage. We evaluated the role of miR-21 in MSC and neuroprotection in ICH, then we found that miR-21 could enhance MSC survival, neurological function recovery and alleviate neuron apoptosis in ICH rats. In addition, we demonstrated that miR-21 could be transported to neuron through exosomes derived from MSCs and target TRPM7 to alleviate the neuron injury after intracerebral hemorrhage. Furthermore, NF-κB pathway is involved in the regulation of miR-21 in neural cells. In conclusion, miR-21 significantly enhance the survival of MSC in ICH and miR-21-MSCs obviously improved neurological function in intracerebral hemorrhage rats, transplantation of miR-21-overexpressing MSCs provides an effective strategy for neuroprotection and treatment of cerebrovascular related diseases.